Engineering Lactococcus lactis for Increased Vitamin K2 Production - Bøe, Cathrine Arnason; Holo, Helge (Frontiers in Bioengineering and Biotechnology, 2020)
Cheese produced with Lactococcus lactis is the main source of vitamin K2 in the Western diet. Subclinical vitamin K2 deficiency is common, calling for foods with enhanced vitamin K2 content. In this study we describe analyses of vitamin K2 (menaquinone) production in the lactic acid bacterium Lactococcus lactis ssp. cremoris strain MG1363. By cloning and expression from strong promoters we have identified genes and bottlenecks in the biosynthetic pathways leading to the long-chained menaquinones, MK-8 and MK-9. Key genes of the biosynthetic menaquinone pathway were overexpressed, singly or combined, to examine how vitamin K2 production can be enhanced. We observed that the production of the long menaquinone polyprenyl side chain limits total menaquinone synthesis rather than production of the napthoate ring (1,4-dihydroxy-2-naphtoic acid, DHNA). Overexpression of genes causing increased ring formation led to overproduction of short chained MK-3, while overexpression of other key genes resulted in enhanced full-length MK-9 production. Of two putatively annotated prenyl diphosphate synthases we pinpoint llmg_0196 (preA) to be important for menaquinone production in L. lactis. The genes mvk, preA, menF and menA were found to be important contributors to menaquinone levels as single overexpression of these genes double and more than triple the total menaquinone content in culture. Combined overexpression of mvk, preA and menA increased menaquinone levels to a higher level than obtained individually. When the overproducing strains were applied for milk fermentations vitamin K2 content was effectively increased 3-fold compared to the wild type. The results provide a foundation for development of strains to ferment foods with increased functional value i.e. higher vitamin K2 content.